The financial performance of Malaysian private institutions of higher education / Mohd Ridzuan Nordin, Lim Yet Mee and Lim Kwee Pheng - Nordin, Mohd Ridzuan; Lim, Yet Mee; Lim, Kwee Pheng (2002)
The revenue of the 29 private institutions of higher education studied grew by 26.76% in financial year 2000. The profit margin and the return on equity were 3.04% and 12.50% respectively. The analysis on the various groupings found that highest revenue group is making profit while the middle revenue group (RM 4 to RM 20 m per year) suffers losses. The profit after tax for this group is non-proportionately higher than its contribution to total revenue, fixed assets and human resource cost. It is also observed that the revenue per value of fixed assets secured by the larger group is lesser than that of the smaller groups suggesting that the smaller institutions are more effective in utilising their fixed assets. It could also mean that the institutions of higher education studied are facing the diminishing rate of return phenomena with respect to investment in fixed assets. The academic programme conducted by the institutions is also a strong determinant of financial performance of the institutions. The private universities have highest revenue per institutions followed by the 3+0 colleges with the normal colleges least. However the universities as a group are losing money while the colleges are not. As a group, the 3+0 colleges have an advantage over the normal colleges especially in terms of profit margin.